Społeczeństwo informacyjne w Unii Europejskiej - Panenka, Alicja (Informational Society in the European Union, 2007)
The purpose of the article is to describe the activities, which are being undertaken at the EU level, to support the transformation towards the informational societies. The level of such transformation in Poland is analysed. In the comparative survey here presented, both the new and already established member countries of the European Union are considered. Then we attempt to determine the position of Poland among its competitors as well as the leaders in the social politics and economy. The relevant initiatives of the Polish government, aimed to assure the effectiveness of the transformational process, are also discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (15); 2007; nr 1166, s. 193-205